ANALISIS PENDAPATAN USAHATANI DAN BIAYA POKOK PRODUKSI PADI RAWA LEBAK DI DESA SERIJABO KECAMATAN SUNGAI PINANG KABUPATEN OGAN ILIR - Aminah Candra Kasih; Wan Abbas Zakaria; Maya Riantini (Lampung University, 2020)
This research aims at determining the farm income and main production cost of rice on lowland swamp in Serijabo Village Sungai Pinang Sub-District. This field research was conducted in February-March 2019. The location was one of central productions in Sungai Pinang Sub-District. The sample size was 51 rice farmers who were selected using simple random sampling method. The data were analyzed by using farm income and main production cost analysis with 95 percent of confidence level. The study showed that the biggest average production of rice was 4,446.35 kg per ha per year with the average of farm income of IDR3,655,271.77. The main production cost of rice per kilogram was IDR825,70 over cash costs and IDR3,682.70 per kg over total costs with 95 percent of confidence level between IDR2,.987.13 per kg and IDR4,335.80 per kg of rice.Key words: farming, income, lowland, production cost, rice